Inflammasome signalling pathway in the regulation of inflammation – its involvement in the development and exacerbation of asthma and chronic obstructive pulmonary disease - Panek, Iga; Liczek, Maciej; Gabryelska, Agata; Rakoczy, Igor; Kuna, Piotr; Panek, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Inflammasomes are multiprotein oligomers, whose main function is the recruitment and activation of caspase-1, which cleaves the precursor forms of interleukin (IL)-1b and IL-18, generating biologically active cytokines. Activation of inflammasome is an essential component of the innate immune response, and according to recent reports it is involved in epithelial homeostasis and type 2 T helper cell (Th2) differentiation. In recent years, the contribution of inflammasome dependent signalling pathways to the development of inflammatory diseases became a topic of multiple research studies. Asthma and chronic obstructive pulmonary disease (COPD) are the most prevalent obstructive lung diseases. Recent studies have focused on inflammatory aspects of asthma and COPD development, demonstrating the key role of inflammasome-dependent processes. Factors responsible for activation of inflammasome complex are similar in both asthma and COPD and include bacteria, viruses, cigarette smoke, and particulate matter. Some recent studies have revealed that NLRP3 inflammasome plays a crucial role, particularly in the development of acute exacerbations of COPD (AECOPD). Activation of NLRP3 inflammasome has been linked with neutrophilic severe steroid-resistant asthma. Although most of the studies on inflammasomes in asthma and COPD focused on the NLRP3 inflammasome, there are scarce scientific reports linking other inflammasomes such as AIM2 and NLRP1 with obstructive lung diseases. In this mini review we focus on the role of molecular pathways associated with inflammasome in the most prevalent lung diseases such as asthma and COPD. Furthermore, we will try to answer the question of whether inhibition of inflammasome can occur as a modern therapy in these diseases.